2012
DOI: 10.1179/1465312512z.0000000009
|View full text |Cite
|
Sign up to set email alerts
|

Enamel colour changes after debonding using various bonding systems

Abstract: Moderate evidence exists that shorter resin tag penetration produces less change in enamel colour following clean-up and polishing. Self-etch primers produce less resin penetration and these systems may produce less iatrogenic colour change in enamel following orthodontic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 15 publications
1
39
0
5
Order By: Relevance
“…In this study, all experimental groups showed color differences that exceeded the threshold of clinical detection between baseline T0 and T1 (group I ∆E=4.93, group II ∆E=5.04, and group III ∆E =9.76). Similar results were reported by Zaher et al (33) where all experimental groups showed significant color change between baseline and finishing which exceeded the threshold for clinical color detection of (∆E= 6.26, Volume 44 -December 2013 ∆E= 6.68, and ∆E =5.67). This was attributed to the change in the refractive index of the enamel caused by the infiltration of the resin tags, which could modify the diffusely reflected light component, thus influencing the color parameters.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, all experimental groups showed color differences that exceeded the threshold of clinical detection between baseline T0 and T1 (group I ∆E=4.93, group II ∆E=5.04, and group III ∆E =9.76). Similar results were reported by Zaher et al (33) where all experimental groups showed significant color change between baseline and finishing which exceeded the threshold for clinical color detection of (∆E= 6.26, Volume 44 -December 2013 ∆E= 6.68, and ∆E =5.67). This was attributed to the change in the refractive index of the enamel caused by the infiltration of the resin tags, which could modify the diffusely reflected light component, thus influencing the color parameters.…”
Section: Discussionsupporting
confidence: 88%
“…Roots were scaled and cleaned of soft tissue debris using handscaler † and then stored in an aqueous solution of thymol (0.1%) at room temperature to prevent dehydration (32) . A black container was used for storage so that any possible effects of light are eliminated (33) .…”
Section: Sample Selection and Preparationmentioning
confidence: 99%
“…Some in vitro studies have concluded that there is no definitive evidence to show the bonding/debonding procedures alone exert significant effect on the colour of both bovine and human tooth enamel . However, other research has indicated that these procedures have a discernible impact on enamel colour . Irrespective of these conflicting conclusions, several reports have emphasized the need for further randomized clinical trials to try to clarify the issue.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 However, other research has indicated that these procedures have a discernible impact on enamel colour. [15][16][17] Irrespective of these conflicting conclusions, several reports have emphasized the need for further randomized clinical trials to try to clarify the issue. In vivo studies have previously revealed colour differences following The results of the present long-term in vivo study indicate that the colour of natural teeth after the first retention year demonstrated significant changes, ranging from 1.4 to 2.1 ΔΕ units.…”
Section: Discussionmentioning
confidence: 99%
“…There are various materials and techniques used for tooth enamel conditioning before bonding orthodontic accessories. In a recent study 2 Egyptian researchers performed an evaluation of whether or not the different methods and materials would alter enamel color after debonding, in addition to verifying the degree of penetration of bonding materials into enamel. The results found showed that self-etching agents presented lower levels of penetration and coloring of enamel after debonding, whereas etching with 37% phosphoric acid for 60 seconds presented the highest level of coloring and infiltration, and showed differences when compared with the same phosphoric acid for a period of 15 seconds.…”
Section: Self-etching Agents Produce Fewer Changes In Enamel Color Afmentioning
confidence: 99%